2010
DOI: 10.1016/j.jvs.2010.07.014
|View full text |Cite
|
Sign up to set email alerts
|

First United States experience of the TX2 Pro-Form thoracic delivery system

Abstract: The Pro-Form delivery system significantly improves endograft conformation to the arch, resulting in minimum bird-beaking even in severely angulated anatomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…9 The Zenith Alpha stent grafts were not used because they were unavailable in the department. This low profile device is one of the newest endografts designed to overcome vascular access issues and also to improve conformability thanks to the new trigger wire release system.…”
Section: Discussionmentioning
confidence: 99%
“…9 The Zenith Alpha stent grafts were not used because they were unavailable in the department. This low profile device is one of the newest endografts designed to overcome vascular access issues and also to improve conformability thanks to the new trigger wire release system.…”
Section: Discussionmentioning
confidence: 99%
“…95 The latter was designed specifically to achieve good proximal apposition due to a diameter reducing tie on the inner curve that forces the stent-graft to partially intussuscept, allowing a more angulated fixation. 94,95 Interestingly, although complete stent-graft apposition was significantly higher in the group that was treated with the Pro-Form delivery system (65% of Pro-Form patients vs 18% Z-Trak vs 6% Gore TAG, p<0.0001), there was no difference in terms of type Ia endoleak occurrence. 94 On the contrary, Ueda et al 89 demonstrated that mean birdbeak length was significantly longer in patients with type Ia or II endoleak (14.3 and 13.9 mm, respectively) than in patients without endoleaks (8.4 mm).…”
Section: Bird-beak Signmentioning
confidence: 91%
“…94,95 Interestingly, although complete stent-graft apposition was significantly higher in the group that was treated with the Pro-Form delivery system (65% of Pro-Form patients vs 18% Z-Trak vs 6% Gore TAG, p<0.0001), there was no difference in terms of type Ia endoleak occurrence. 94 On the contrary, Ueda et al 89 demonstrated that mean birdbeak length was significantly longer in patients with type Ia or II endoleak (14.3 and 13.9 mm, respectively) than in patients without endoleaks (8.4 mm). The bird-beak sign might be a precursor of an increased risk of rupture and therefore demands close follow-up.…”
Section: Bird-beak Signmentioning
confidence: 91%
See 1 more Smart Citation
“…15,16 However, this lower incidence of malalignment was not reflected in a decreased type I endoleak rate. The Zenith Alpha device is loaded on a precurved, triple axial deployment system, which should make the deployment easier and more accurate, potentially reducing misdeployment and malapposition.…”
mentioning
confidence: 93%